EFEK KOLAGEN DARI BERBAGAI JENIS TULANG IKAN TERHADAP KUALITAS MIOFIBRIL PROTEIN IKAN SELAMA PROSES DEHIDRASI [Effect of Various Fish Bone Collagens on the Quality of Myofibril Fish Protein During Dehydration Process] - Yudhomenggolo Sastro Darmanto; Tri Winarni Agustini; Fronthea Swastawati (Jurnal Teknologi dan Industri Pangan, 2012)
Increase in fish fillet export in Indonesia has caused an increase in its waste such as bones, spines, skin and entrails of fish. Fish bones can be processed by demineralization to produce collagen, an important food additive. The effect of addition of 5% of collagen obtained from fresh water, brackish water and sea water fish bone on the fish protein miofibril of grouper was investigated in this research. Water sorption isotherm, Ca-ATPase activity, gel strength, water holding capacity, folding test and viscosity during dehydration process were evaluated. The results showed that collagens made from various fish bones have different Ca-ATPase activity. The reduction rate of Ca-ATPase activity were in accordance with the reduction of water sorbtion isotherm, gel forming ability, water holding capacity, viscosity and folding test during dehydration process.